2002
DOI: 10.1074/jbc.m202974200
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Repressor Activating Transcription Factor 3 Protects Human Umbilical Vein Endothelial Cells from Tumor Necrosis Factor-α-induced Apoptosis through Down-regulation ofp53 Transcription

Abstract: Activating transcription factor 3 (ATF3) is a transcriptional repressor that is rapidly induced in cells exposed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
88
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(92 citation statements)
references
References 46 publications
3
88
1
Order By: Relevance
“…It is interesting to note that ATF3 directly binds p53 and represses the p53-dependent trans-activation of the collagenase gene promoter 29) . Kawauchi et al 30) also demonstrated that ATF3 protected endothelial cells from TNF-α-induced apoptosis by downregulating p53. Based on our TUNEL, RT-PCR and western blot findings, we propose that it is possible that since P53 expression was not significantly different from the control in the DEHP 100 mg/kg/day group (Figs.…”
Section: Discussionmentioning
confidence: 97%
“…It is interesting to note that ATF3 directly binds p53 and represses the p53-dependent trans-activation of the collagenase gene promoter 29) . Kawauchi et al 30) also demonstrated that ATF3 protected endothelial cells from TNF-α-induced apoptosis by downregulating p53. Based on our TUNEL, RT-PCR and western blot findings, we propose that it is possible that since P53 expression was not significantly different from the control in the DEHP 100 mg/kg/day group (Figs.…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, ATF3 is normally expressed at a steady state in quiescent cells. It has traditionally been related to cell survival and/or apoptosis, stress, DNA damage, homeostasis, wound healing, cell adhesion, inflammation, nutrient limitation, and chemical exposure (32)(33)(34)(35)(36). Moreover, overexpression of ATF3 suppresses cell growth, by slowing the progression of cells from G1 to S phase, and it has been related to pro-apoptotic events and in the regulation of cell fate (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…ATF3-and p15 PAF -expressing constructs have been described earlier. 16,28 Transfection experiments were carried out in 24-well plate (60 000) cells, using the Lipofectamine 2000 reagent (Invitrogen). When indicated, cells were UVC-irradiated (5 J/m 2 , Vilber Lourmat) the day after transfection.…”
Section: Methodsmentioning
confidence: 99%